Viability of Loma salmonae (Microsporidia) under laboratory conditions - Shaw, Ross W.; Kent, Michael L.; Adamson, Martin L. (My University, 2000)
The viability of the fish-infecting microsporidian Loma salmonae Morrison and Sprague, 1981 was determined under laboratory conditions by polar filament extrusion and infectivity to chinook salmon (Oncorhynchus tshawytscha). Extrusion rates of isolated spores decreased from 51.0% to 0.0% by 100 days after storage in fresh or sea water at 4 °C. Spores stored up to 95 days in either solution infected 80.0–100.0% of exposed chinook, although no spores infected fish at 100 days in one trial. Viability in Earl's balanced salt solution was tested up to 50 days, with 23.7% of spores extruding filaments and 80.0% of exposed chinook becoming infected. Spores frozen to −20 °C or −70 °C were unable to infect fish.
Keywords: laboratory condition; salt solution; balance salt; balance salt solution; Chinook salmon